Uncertainty of phosphorus loadings estimation using vollenweider model for reservoir euthrophication control - Shamsudin, Supiah; Harun, Sobri; Ab. Rahman, Azmi (Faculty of Civil Engineering, 2009)
Eutrophication process downgraded lake or reservoir water quality, if the system is not monitored and managed properly. Recent investigation seems to favor phosphorus as the limiting factor for reservoir productivity. The purpose of this study is to estimate the uncertainty of phosphorus loadings for the Layang reservoir using Vollenweider-IHACRES model. The incorporation of IHACRES Model had helped to compute better hydrological estimation. This model is used to predict the streamflow into the reservoirs that later be used in the Vollenweider model. Rainfall data were obtained from the Department of Irrigation and Drainage Malaysia for the Station 1539001, Loji air Sungai Layang. Five water samples were taken randomly near the inlet and upstream of reservoir. The water samples were tested with reagent phos Ver 3 phosphate using DR 4000 (Hach Co. CO 80539-9987, USA) to indicate the dissolved phosphorus content in mg/l. The total phosphorus concentration obtained from the three site visits were observed. The average phosphorus content was 0.214 mg/l. The highest phosphorus content observed was 0.622 mg/l and the lowest concentration was 0.053 mg/l. Fuzzy membership function is then used to describe phosphorus content, hydraulic loadings and the phosphorus loadings that represent the current conditions of the reservoir. By using fuzzy membership function, a range of estimation could be obtained. The most likely range of phosphorus content obtained was 0.1 mg/l to 0.3 mg/l and for hydraulic loadings was 1350 m/yr to 1400 m/yr. Estimated phosphorus loadings range from 0.26 g/m2/yr to 0.81 g/m2/yr (7.81 ton/yr to 24.28 ton/yr). The average phosphorus content was 0.214 mg/l and average hydraulic loading was 1452.25 m/yr. The average phosphorus loading calculated was 0.6g/m2/yr, within the estimated range of 0.26g/m2/yr to 0.81g/m2/yr. The largest bias from the IHACRES model simulation is -0.5546 mm/day and the smallest bias is -0.0076 mm/day. The highest R2 value is 0.9925 while the lowest is 0.9208. Both statistics showed that the model is able to perform well. This fuzzy phosphorus loadings estimation will help lake water quality improvement and management in the future. In order to ensure the phosphorus level reduction and overall lake water quality, the development and overall activities within the watershed should be properly and systematically managed.